Mapping and Analysis of the Sorghum Value Chain in Tehuledere District, Amhara Region, Ethiopia - Teferi, Wondale Habtamu (iRASD Journal of Management, 2024)
This study describes sorghum-cultivating households and assesses factors affecting different activities of the sorghum value chain in the Tehuledere district of the Amhara region, Ethiopia. Primary data were obtained by administering structured questionnaires and interviews to 297 respondents across the value chain from smallholder farmers, agro-dealers, traders, retailers, wholesalers, and processors. In this context, the study was able to map the value chain to establish the main actors involved and their relationships. The current value chain has Input Suppliers, Producers/Farmers, Wholesalers/Distributors, Transporters, Processors, and Consumers. Some issues were identified as input supply with some inefficiency and marketing and processing channels as supply was interrupted and producer prices were low. This implies increasing interactions with extension agents to enhance the use of better sorghum seed varieties and fertilizers. The proposed solutions are the cooperation of different actors, higher levels of investment in R&D, better extension services, private sector engagement, encouraging legislation, and infrastructure development to overcome institutional weaknesses.